FIQH AL-á¸¤Aá¸ŒARAH REVIEW ON THE PREVENTION OF LGBT: Critical Study of the Phenomena of LGBT Campaign Efforts in Social Media - Rois, Choirur; Zainuri, Ahmad; Dewi, Marisa Santi (AL-TAHRIR, 2023)
Lesbian, Gay, Bisexual, and Transgender (LGBT) campaigns on various social media are getting more massively echoed by pro-LGBT groups. The LGBT community channels their creativity and expression to gain recognition and acceptance from netizens through Instagram, Tiktok, and other social media. Responding to this phenomenon, Indonesia, as a Muslim-majority country, in article 85 of the Family Resilience Bill, defines LGBT as an act of sexual deviance. As the science of law in Islam, Fiqh does not only talk about the halal and haram of a job. Law provisions prevent deviations from the occurrence of human roles and functions based on their nature. Thus, the authors examine the construction of fiqh law to prevent and raise the grasp of Lesbian, Gay, Bisexual, and Transgender (LGBT) people on social media. This study employed a sociological approach to Islamic law based on phenomenological and literature studies. The results of this study indicate: (1) massive campaigns and LGBT hegemony in social media harm the sociocultural orientation of future generations, (2) the legal construction of fiqh al-á¸¥aá¸arah as a solution in providing awareness and prevention of LGBT campaigns on social media, (3) there is a spirit of collaboration between the concept of fiqh al-á¸¥aá¸arah and positive law in Indonesia in preventing and arousing LGBT campaigns in social media.